An Agenda in Motion: Women’s Issues in Latin American Higher Education - Maldonado-Maldonado, Alma; Acosta, Felicitas (International Higher Education, 2018)
Women in Latin America have experienced physical and psychological violence; discrimination; lack of equal opportunities; less recognition for their work, abilities, and capacities. The #MeToo and Time's Up movements (2017) are dealing with the issue of women's role in present-day society and highlight cases of male power towards women. This article offers a reflection on this discussion at universities in the region.